Anti-diabetic rosiglitazone remodels the adipocyte transcriptome by redistributing transcription to PPARγ-driven enhancers - Step, Sonia E. (Cold Spring Harbor Laboratory Press, 2014)
Rosiglitazone (rosi) is a powerful insulin sensitizer, but serious toxicities have curtailed its widespread clinical use. Rosi functions as a high-affinity ligand for peroxisome proliferator-activated receptor γ (PPARγ), the adipocyte-predominant nuclear receptor (NR). The classic model, involving binding of ligand to the NR on DNA, explains positive regulation of gene expression, but ligand-dependent repression is not well understood. We addressed this issue by studying the direct effects of rosi on gene transcription using global run-on sequencing (GRO-seq). Rosi-induced changes in gene body transcription were pronounced after 10 min and correlated with steady-state mRNA levels as well as with transcription at nearby enhancers (enhancer RNAs [eRNAs]). Up-regulated eRNAs occurred almost exclusively at PPARγ-binding sites, to which rosi treatment recruited coactivators, including MED1, p300, and CBP. In contrast, transcriptional repression by rosi involved a loss of coactivators from eRNA sites devoid of PPARγ and enriched for other transcription factors, including AP-1 factors and C/EBPs. Thus, rosi activates and represses transcription by fundamentally different mechanisms that could inform the future development of anti-diabetic drugs.